Ontological Terror Blackness, Nihilism and Emancipation - L. Warren, Calvin (Duke University Press, 2018)
In Ontological Terror Calvin L. Warren intervenes in Afro-pessimism, Heideggerian metaphysics, and black humanist philosophy by positing that the "Negro question" is intimately imbricated with questions of Being. Warren uses the figure of the antebellum free black as a philosophical paradigm for thinking through the tensions between blackness and Being. He illustrates how blacks embody a metaphysical nothing. This nothingness serves as a destabilizing presence and force as well as that which whiteness defines itself against. Thus, the function of blackness as giving form to nothing presents a terrifying problem for whites: they need blacks to affirm their existence, even as they despise the nothingness they represent. By pointing out how all humanism is based on investing blackness with nonbeing-a logic which reproduces antiblack violence and precludes any realization of equality, justice, and recognition for blacks-Warren urges the removal of the human from its metaphysical pedestal and the exploration of ways of existing that are not predicated on a grounding in being.